Motivation towards the involvement of household in recycling activities at Seberang Perai Tengah, Penang / Nurul Atiqah Shahrul Zaman and Nurul Dalina Mohamad Ristak - Shahrul Zaman, Nurul Atiqah; Mohamad Ristak, Nurul Dalina (2020)
This research study was carried out to explore the motivation towards the involvement of household in recycling activities at Seberang Perai Tengah, Penang. Researchers had examined four motivations that influence the household to be involved in recycling activities at their residential areas. Motivations included are convenience, attitude, knowledge and social pressure.This study was a descriptive research study. Quantitative data collection method and convenience sampling method had been used. The target population is the households in Seberang Perai Tengah, Penang area especially in Bukit Mertajam. This study used primary data collection method and secondary data collection method. Journal, internet research and text book had been used as secondary data collection. Questionnaire-based survey was used and 270 sets of questionnaires were distributed to respondents and the respond rate was 100%. The questionnaire being returned and the data will be analysed by using SPSS. Descriptive analysis, reliability test, Pearson correlation coefficient test and multiple regression analysis were being chosen as data analysis techniques. The questions and scales in questionnaires were considered to be reliable and all the hypothesis proposed in this research were accepted.